PtdIns(4,5)P2 stabilizes active states of GPCRs and enhances selectivity of G-protein coupling - Yen, H; Hoi, K; Liko, I; Hedger, G; Horrell, M; Song, W; Wu, D; Heine, P; Warne, T; Lee, Y; Carpenter, B; Plückthun, A; et al. (Springer Nature, 2018)
G-protein-coupled receptors (GPCRs) are involved in many physiological processes and are therefore key drug targets1. Although detailed structural information is available for GPCRs, the effects of lipids on the receptors, and on downstream coupling of GPCRs to G proteins are largely unknown. Here we use native mass spectrometry to identify endogenous lipids bound to three class A GPCRs. We observed preferential binding of phosphatidylinositol-4,5-bisphosphate (PtdIns(4,5)P2) over related lipids and confirm that the intracellular surface of the receptors contain hotspots for PtdIns(4,5)P2 binding. Endogenous lipids were also observed bound directly to the trimeric Gαsβγ protein complex of the adenosine A2A receptor (A2AR) in the gas phase. Using engineered Gα subunits (mini-Gαs, mini-Gαi and mini-Gα12)2, we demonstrate that the complex of mini-Gαs with the β1 adrenergic receptor (β1AR) is stabilized by the binding of two PtdIns(4,5)P2 molecules. By contrast, PtdIns(4,5)P2 does not stabilize coupling between β1AR and other Gα subunits (mini-Gαi or mini-Gα12) or a high-affinity nanobody. Other endogenous lipids that bind to these receptors have no effect on coupling, highlighting the specificity of PtdIns(4,5)P2. Calculations of potential of mean force and increased GTP turnover by the activated neurotensin receptor when coupled to trimeric Gαiβγ complex in the presence of PtdIns(4,5)P2 provide further evidence for a specific effect of PtdIns(4,5)P2 on coupling. We identify key residues on cognate Gα subunits through which PtdIns(4,5)P2 forms bridging interactions with basic residues on class A GPCRs. These modulating effects of lipids on receptors suggest consequences for understanding function, G-protein selectivity and drug targeting of class A GPCRs.